A Numerical Case Study on Boundary Effect in Test and Simulation of Seismic Hydrodynamic Pressure on Pier. Issue 1 (February 2021) - Liu, Haiming; Tao, Xiaxin; Qin, Yifang; Tao, Zhengru
Abstract: Total 12 finite element models are built for piers of rectangular and elliptical sections in water with infinite boundary condition or with elastic boundaries and longitudinal size 3 m, 5 m, 7.5 m, 10 m and 15 m respectively. Responses of the models are calculated by numerical water - pier interaction coupling procedure. The result hydrodynamic pressures of nodes on the central line of the pier upstream faces at 8 depths show that the pressures on models with elastic boundaries are getting close to that with infinite boundary as the longitudinal size increasing, and the 15 m length is long enough for tank in shaking table test to prevent the disturbance of boundary wave on the maximum absolute value of hydrodynamic pressure.